Using gasliquid chromatrography to choose solvents for separation of biazeotropic benzene – perfluorobenzene mixture by extractive rectification - P. G. Rumyantsev; V. I. Zhuchkov; A. K. Frolkova; A. V. Anisimov (Тонкие химические технологии)
Gas-liquid chromatography was used for estimating the selectivity of solvents for the separation of biazeotropic benzene - perfluorobenzene mixture based on extractive rectification.The selected optimal solvents enable two theoretically feasible variants of the mixture separation.